Preliminary analysis of hippocampus synaptic apoptosis and microglial phagocytosis induced by severe restraint stress - Shingo Enomoto; Masahiro Ohgidani; Noriaki Sagata; Shogo Inamine; Takahiro A. Kato (Wiley, 2023)
Abstract Aim Several studies reported stress‐induced microglial phagocytosis, but the biochemical mechanisms by which stress alters microglial synaptic phagocytosis are not fully uncovered. Local or limited apoptosis without cell death was observed at neuronal synapses in previous studies, and proposed as an upstream mechanism for microglial synapse elimination. In this micro‐report, we aimed to preliminary examine local synaptic apoptosis in the mouse hippocampus following severe restraint stress, and its effect on microglial phagocytosis. Methods Mice were exposed to 10‐day water immersion restraint stress (WIRS). Brain sections including stratum lucidum in the hippocampal CA3 subfield were stained with antibodies against cleaved caspase 3, ionized calcium‐binding adapter molecule1 (Iba1), lysosomal‐associated membrane protein1 (LAMP1), vesicular glutamate transporter1 (VGLUT1). Co‐localization among these proteins were calculated. Results Our image analysis revealed that synaptic apoptosis was increased while there were no significant changes in microglial phagocytic activity and synaptic phagocytosis following 10‐day WIRS. Conclusion Severe restraint stress enhanced pre‐synaptic apoptosis in mouse CA3 stratum lucidum region, but did not promote microglial phagocytosis. The phenomenon microglia fail to phagocytose weakened and unnecessary synapses may be related to pathology of stress.